2009
DOI: 10.1007/s10047-009-0467-2
|View full text |Cite
|
Sign up to set email alerts
|

Artificial vision by direct optic nerve electrode (AV-DONE) implantation in a blind patient with retinitis pigmentosa

Abstract: The purpose of this study was to evaluate the efficacy and safety of artificial vision by using a direct optic nerve electrode (AV-DONE) in a blind patient with retinitis pigmentosa (RP). This device, comprising three wire electrodes (0.05 mm in diameter), was implanted into the optic disc of a patient with RP with no light perception vision and the device was left implanted. Six months later, visual sensations were elicited by electrical stimulation through each electrode and the thresholds for the phosphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The alternative penetrating electrodes have had less functional vision success. Whilst it has been shown that intra-orbital optic nerve stimulation with penetrating electrodes can evoke cortical responses in rabbits [ 87 ] and can generate perception of phosphenes in humans [ 84 ], patients implanted with these devices have not been able to use these phosphenes to improve their functional vision and were unable to detect or localise objects with the device.…”
Section: Optic Nerve Prosthesesmentioning
confidence: 99%
“…The alternative penetrating electrodes have had less functional vision success. Whilst it has been shown that intra-orbital optic nerve stimulation with penetrating electrodes can evoke cortical responses in rabbits [ 87 ] and can generate perception of phosphenes in humans [ 84 ], patients implanted with these devices have not been able to use these phosphenes to improve their functional vision and were unable to detect or localise objects with the device.…”
Section: Optic Nerve Prosthesesmentioning
confidence: 99%
“…These subjects were able to recognize simple patterns projected onto a screen, 26 localize and discriminate objects 55,59–61 . An alternative to the cuff‐electrode is the insertion of multiple penetrating electrodes onto the optic nerve and optic disc 62–68 . Stimulation of these electrodes in the acute setting have produced the sensation of phosphenes 66 …”
Section: Optic Nerve/tract Prosthesismentioning
confidence: 99%
“…An alternative to the cuff‐electrode is the insertion of multiple penetrating electrodes onto the optic nerve and optic disc 62–68 . Stimulation of these electrodes in the acute setting have produced the sensation of phosphenes 66 …”
Section: Optic Nerve/tract Prosthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Because some of the inner retinal neurons are somewhat preserved in RP patients, 1,2 several research groups are investigating whether an intraocular retinal prosthesis can restore vision in these patients by activating the functioning neurons. [3][4][5][6][7] We have developed a new method of stimulating the retina called suprachoroidal-transretinal stimulation (STS), 8 and experiments on normal rabbits 9,10 and RCS rats 11 have shown that electrically evoked potentials (EEPs) can be elicited by stimulating the retina by STS. However, a middle-sized animal model with damage predominantly in the outer retinal layer, as is observed in eyes of RP patients, is needed to evaluate the effectiveness of the STS system more completely.…”
mentioning
confidence: 99%